Experimental Combined Immunotherapy of Tumours with Major Histocompatibility Complex Class I Downregulation - Grzelak, Adrianna; Polakova, Ingrid; Smahelova, Jana; Vackova, Julie; Pekarcikova, Lucie; Tachezy, Ruth; Smahel, Michal (International journal of molecular sciences, 2018)
Combined immunotherapy constitutes a novel, advanced strategy in cancer treatment. In this study, we investigated immunotherapy in the mouse TC-1/A9 model of human papillomavirus type 16 (HPV16)-associated tumors characterized by major histocompatibility complex class I (MHC-I) downregulation. We found that the induction of a significant anti-tumor response required a combination of DNA vaccination with the administration of an adjuvant, either the synthetic oligodeoxynucleotide ODN1826, carrying immunostimulatory CpG motifs, or α-galactosylceramide (α-GalCer). The most profound anti-tumor effect was achieved when these adjuvants were applied in a mix with a one-week delay relative to DNA immunization. Combined immunotherapy induced tumor infiltration with various subsets of immune cells contributing to tumor regression, of which cluster of differentiation (CD) 8⁺ T cells were the predominant subpopulation. In contrast, the numbers of tumor-associated macrophages (TAMs) were not markedly increased after immunotherapy but in vivo and in vitro results showed that they could be repolarized to an anti-tumor M1 phenotype. A blockade of T cell immunoglobulin and mucin-domain containing-3 (Tim-3) immune checkpoint had a negligible effect on anti-tumor immunity and TAMs repolarization. Our results demonstrate a benefit of combined immunotherapy comprising the activation of both adaptive and innate immunity in the treatment of tumors with reduced MHC-I expression.
Keywords: MHC antigeny I. třídy; Animals; Female; Cell Line, Tumor; galaktosylceramidy; makrofágy; ženské pohlaví; Adjuvants, Immunologic; Oligodeoxyribonucleotides; Galactosylceramides; Immunotherapy; Macrophages; CD8-Positive T-Lymphocytes; Mice; experimentální nádory; myši; Down-Regulation; CD8-pozitivní T-lymfocyty; imunoterapie; oligodeoxyribonukleotidy; down regulace; zvířata; Mice, Inbred C57BL; Histocompatibility Antigens Class I; adjuvancia imunologická; Neoplasms, Experimental; nádorové buněčné linie; myši inbrední C57BL